ANTI-RACISM ON THE CHARACTER OF HERMAN BOONE IN REMEMBER THE TITANS DIRECTED BY BOAZ YAKIN - Puspitaningrum, Winda Febiana (LANTERN (Journal on English Language, Culture and Literature), 2014)
Racism has existed in American society for many years, especially in Alexandria, Virginia. There is segregation between blacks and whites there. However, a federal mandate to integrate the two schools into one, TC Williams. Herman Boone is the new head coach at T.C. Williams, who wanted to bring together all the players, black and white.The purpose of this paper is to describe the intrinsic aspect, get an overview of the anti-racism of Herman Boone, and analyze the social impact in Alexandria. Researcher obtains data by watching Remember the Titans as the primary data. Secondary data derives from theories related to anti-racism, motives, attitudes, social influence, and social nature. Finally, the researcher could see a big impact in the community of Herman Boone attitude that spreads through football.This study suggests that anti-racism attitude of Herman Boone can affect people in Alexandria. Boone changed the mindset of the people slowly. First, Boone changes the mindset of his football team and makes the team as a solid team. Second, with remarkable achievements earned his team, Boone changes people's mindsets through eufouria os his team’s victory. His anti-racism Boone is also influenced by motives that arise due to the influence of the social characteristics of North Carolina society, where Boone lived before he and his family moved to Alexandria.